(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Capillaroscopy is a method of visual observation of peripheral vessels. Capillary blood circulation is examined in the nail bed (area), where most capillaries are well visible. This article will give you the skills and knowledge about capillaroscopy.